Pattern of Sputum Bacteriology in Acute Exacerbations of Chronic Obstructive Pulmonary Disease (Journal of Enam Medical College, 2018)
Background: Chronic obstructive pulmonary disease (COPD) is a major cause of chronic morbidity and mortality worldwide. Acute exacerbation is an acute and sustained worsening of a patient’s condition from a stable state (beyond normal day-to-day variations) and it is caused in majority by infectious agents, particularly bacteria.Objectives: The aim of this study was to find out the pattern of sputum bacteriology and antibiotic sensitivity in patients admitted into respiratory ward of Enam Medical College Hospital (EMCH) with acute exacerbation of COPD (AECOPD).Materials and Methods: This study included 60 patients who presented with acute exacerbation of COPD. The patients were classified into several groups according to different variables, such as age, pack years, severity, O2 saturation on admission, sputum type. Bacteriological investigations were performed for all patients and included gram staining together with culture and sensitivity testing of all sputum samples.Results: Klebsiella pneumoniae was the most common isolate in patients with COPD exacerbations admitted into the respiratory ward of Enam Medical College & Hospital followed by Staphylococcus aureus and Streptococcus pneumoniae. Three cases of Pseudomonus aeruginosa were detected. Gentamicin and meropenem were the most sensitive antibiotics in all patient groups in the ward. Majority of Klebsiella pneumoniae, Streptococcus pneumoniae and Staphylococcus aureus were sensitive to ceftriaxone, levofloxacin and moxifloxacin.Conclusion: This study reveals that gentamicin, ceftriaxone and moxifloxacin can be the drugs of choice in treating AECOPD in our setting.J Enam Med Col 2018; 8(2): 80-84